Martin Heidegger and the Question of Literature Toward a Postmodern Literary Hermeneutics - Spanos, William V. (Indiana University Press, 1979)
For half a century, Martin Heidegger's philosophical thought has been a towering-even revolutionary-presence on the European scene, yet in the United States and England complete understanding of his enormous importance is still limited. The essays in this volume constitute the first systematic effort to relate the applicability of Heidegger's hermeneutic thought and practice to questions concerning the nature and function of language, the interpretation of literary texts, and the "crises of criticism" central to the postmodern situation. Distinguished philosophers and literary critics address themselves to these issues in the context of the poetics of New Criticism-which they collectively call into question-and in light of the spirited dialogue between proponents of the new currents of hermeneutic and critical thinking-phenomenological, structuralist , deconstructionist -that are vying to replace New Criticism. The volume includes Heidegger's essay "The Age of the World View," translated by Mar jorie Grene; a photographic essay by Donald Bell; and contributions by Stanley Corngold, Frances C. Ferguson, Michael Gelven, Karsten Harries, Albert Hofstadter, David Couzens Hoy, David Farrell Krell, Donald G. Marshall, Richard E. Palmer, Joseph N . Riddel, Alvin H. Rosenfeld, Reiner Schiirmann, Armand Schwerner, William V. Spanos, and Gerry Stahl.